Combination of epidermal growth factor receptor mutation and the presence of high-grade patterns is associated with recurrence in resected stage I lung adenocarcinoma. (10th March 2022) - Kondo, Yasuto; Ichinose, Junji; Ninomiya, Hironori; Hashimoto, Kohei; Matsuura, Yosuke; Nakao, Masayuki; Ishikawa, Yuichi; Okumura, Sakae; Satoh, Yukitoshi; Mun, Mingyon
Abstract: OBJECTIVES: This study aimed to evaluate the prognostic impact of the combination of epidermal growth factor receptor (EGFR) mutation and the presence of high-grade patterns (solid or micropapillary component) in resected stage I lung adenocarcinoma. METHODS: Patients who underwent curative resection for pathological stage I lung adenocarcinoma and EGFR mutation analysis were included in this study. The impact of the combination of EGFR mutation and the presence of >5% high-grade patterns on recurrence-free survival (RFS) was retrospectively analysed using Cox proportional hazards model and propensity score-matched analysis. RESULTS: Among the included 721 patients, EGFR mutations were positive in 380 (52.7%). In the EGFR-mutated group, cases with high-grade patterns showed poorer RFS than those without (5-year RFS, 77.7% vs 92.5%, P < 0.001), whereas there were no significant prognostic differences in the EGFR wild-type group (5-year RFS, 89.8% vs 88.2%, P = 0.807). Multivariable analyses revealed that the combination of EGFR mutations and the presence of high-grade patterns was associated with poor RFS (hazard ratio = 1.655, P = 0.035). Furthermore, EGFR mutation was associated with poor RFS in the group with high-grade patterns (hazard ratio = 2.108, P = 0.008). After propensity score matching, EGFR-mutated cases with high-grade patterns showed poorer RFS ( P = 0.028). CONCLUSIONS: The combination of EGFR mutation and the presence of high-grade patterns was associated with recurrence in resected stage I lung adenocarcinoma. Histological subtypes, including minor components, should be considered when evaluating the risk of recurrence in patients with EGFR-mutated lung adenocarcinoma. Abstract : Lung cancer is the most common cause of cancer-related death worldwide, with 1 378 400 deaths reported annually.